Applied Management Control Systems for Agile Wedding Project Management: Case Study of LZ Service - Zahra N.A KAMILAH; Alvanov Z. MANSOOR (Communications of International Proceedings, 2021)
LZ Service is a specialized wedding enterprise which performs wedding gallery is located in Bandung, Indonesia since late of 2016. Unlike common retail fashion designer, LZ Service applied agile project management in form of custom-made rent to order as their creative financing. Stagnant business growth from 2018 until 2020 has been faced by LZ Service. It can be seen from the decreasing wedding project. This research used a qualitative method which is aimed to solve the stagnant business growth by improvement strategy in implementing agile project management. The agile project management was evaluated in internal and external analysis to recognized the main problem. Internal analysis was conducted by using business model canvas analysis and business process analysis. And external analysis was conducted by Porter’s Five Force, competitor analysis and customer analysis. It turned out that LZ Service failed to absorb more wedding projects because the existing attire collection could not provide the wanted specification of potential clients due to the fewer number of attire collection. It might be easy to increase production capacity. But, all the final product from production process will be inventory to be rented. As the custom-made rent to order projects increase, there will be more wedding attire inventory in wedding gallery which lead into more complex management. Management problem becomes priority to be solved because there has not been a control design which supports more complex business process. By using Levers of Controls Framework in imposing the control within the project agility in order to succeed the project.
Keywords: agile project management; levers of control; management control systems; wedding gallery.